A Tale of Umrah Pilgrims Fraud in Indonesia: a Narrative Review Indicating and Anticipating “Fake Bureau” - Ardani, Mochammad; Setiawan, Dani; Munir, Muhammad Misbachul; Fitria, Shoimatul (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The umrah bureau sector in Indonesia has great business potential. The increasing number of umrah pilgrims are not accompanied by a level of literacy towards the credibility of the bureau. This raises problem in the form of umrah bureau business practices that are illegal. A lot of fraud cases has caused huge losses to the pilgrims as consumers. This study aims to reveal the factors that causes umrah bureau fraud and formulate anticipatory steps for bureau that indicated fake. The method used is narrative review by elaborating previous research, literature studies, and also supporting database of cases that validate. This research composed by 35 literatures synthesized. The characteristics of the umrah bureau which are indicated fake, including: 1) sloping prices accompanied by promos; 2) travel legality; and 3) ponzi business model. To anticipate, prospective pilgrims should not be tempted by the promos offered by bureau. Prospective pilgrims must also dig up information related to permits, track records and feedback, as well as transparency of facilities that will be provided by the bureau. Regulators must tighten supervision of the business climate through cooperation with associations of umrah organizers in the local area. That way, consumer protection for the umrah bureau will be more secure.